Does childhood schooling affect old age memory or mental status? Using state schooling laws as natural experiments. Issue 6 (13th May 2008) - Glymour, M M; Kawachi, I; Jencks, C S; Berkman, L F
Abstract : Background: The association between schooling and old age cognitive outcomes such as memory disorders is well documented but, because of the threat of reverse causation, controversy persists over whether education affects old age cognition. Changes in state compulsory schooling laws (CSL) are treated as natural experiments (instruments) for estimating the effect of education on memory and mental status among the elderly. Changes in CSL predict changes in average years of schooling completed by children who are affected by the new laws. These educational differences are presumably independent of innate individual characteristics such as IQ. Methods: CSL-induced changes in education were used to obtain instrumental variable (IV) estimates of education's effect on memory (n = 10 694) and mental status (n = 9751) for white, non-Hispanic US-born Health and Retirement Survey participants born between 1900 and 1947 who did not attend college. Results: After adjustment for sex, birth year, state of birth and state characteristics, IV estimates of education's effect on memory were large and statistically significant. IV estimates for mental status had very wide confidence intervals, so it was not possible to draw meaningful conclusions about the effect of education on this outcome. Conclusions: Increases in mandatory schooling lead to improvements in performance on memory tests many decades after school completion. These analyses condition on individual states, so differences in memory outcomes associated with CSL changes cannot be attributed to differences between states. Although unmeasured state characteristics that changed contemporaneously with CSL might account for these results, unobserved genetic variation is unlikely to do so.